2016
DOI: 10.1002/clc.22534
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction and Racial Disparities in Mortality and Adverse Cardiovascular Disease Outcomes

Abstract: Background: The contribution of arterial endothelial dysfunction (ED) to increased cardiovascular disease (CVD) risk among Blacks is not known. Hypothesis: We investigated whether peripheral arterial ED explains racial disparity in CVD events. Methods: Data from the Heart Strategies Concentrating on Risk Evaluation (Heart SCORE) study was used. Endothelial dysfunction was assessed by the Framingham reactive hyperemia index (fRHI), measured using pulse amplitude tonometry (PAT). Lower values of fRHI indicate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
(77 reference statements)
3
13
0
Order By: Relevance
“…Our findings are consistent with other studies, which have similarly found increased CVH to be associated with the decreased burden of subclinical CVD . Despite significant racial differences in prevalence of ideal CVH factors, endothelial function, and markers of subclinical CVD (demonstrated by us and prior reports), we did not find strong evidence for difference in the association between ideal CVH and these outcomes between blacks and whites, consistent with other reports . This study contributes to the developing body of evidence supporting AHAs Life's Simple 7 paradigm of focusing on promotion of overall CVH over a sole focus on single risk factors CVD prevention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with other studies, which have similarly found increased CVH to be associated with the decreased burden of subclinical CVD . Despite significant racial differences in prevalence of ideal CVH factors, endothelial function, and markers of subclinical CVD (demonstrated by us and prior reports), we did not find strong evidence for difference in the association between ideal CVH and these outcomes between blacks and whites, consistent with other reports . This study contributes to the developing body of evidence supporting AHAs Life's Simple 7 paradigm of focusing on promotion of overall CVH over a sole focus on single risk factors CVD prevention.…”
Section: Discussionsupporting
confidence: 91%
“…It is not clear if the trend toward stronger differences for CAC and fRHI seen among whites is real and if the lack of statistical significance in our study is because of limitation in power. Given the known difference in CAC and fRHI between blacks and whites, as well as racial differences in ideal CVH variables and CVD outcomes, these findings would merit further evaluation in larger studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, the prevalence in our study was slightly higher than that observed in a similar age group in the NHANES . Similarly, the mean central retinal venule equivalent (CRVE) in our cohort is consistent with a range of other studies, as was our mean F‐RHI score, and the prevalence of MetS …”
Section: Discussionsupporting
confidence: 92%
“…The Dunedin 38 Indeed, the prevalence in our study was slightly higher than that observed in a similar age group in the NHANES. 38 Similarly, the mean central retinal venule equivalent (CRVE) in our cohort is consistent with a range of other studies, 5 as was our mean F-RHI score, 8,39 and the prevalence of MetS. 40 The strengths of this study include the use of a birth cohort with a very high retention rate, together with comprehensive objective data on periodontitis at ages 32 and 38, and on cardiometabolic risk markers at age 38.…”
Section: Discussionsupporting
confidence: 86%